Transforming Healthcare: A Comprehensive Review of Augmented and Virtual Reality Interventions - Aristeidis Petrakis; Lefteris Koumakis; Eleni Kazantzaki; Haridimos Kondylakis (Sensors, 2025)
Augmented reality (AR) and virtual reality (VR) technologies have rapidly expanded within healthcare due to their innovative capabilities for enhancing patient care, medical training, and health outcomes. This systematic review synthesizes quantitative studies published post-2020, explicitly investigating AR and VR healthcare interventions. The review identifies, evaluates, and summarizes the effectiveness of these interventions, highlighting their clinical implications, outcomes, and implementation challenges. Twenty eligible studies were included, examining various health conditions such as cardiopulmonary resuscitation training, mental health disorders, stroke rehabilitation, and orthopedic recovery. Findings indicate generally positive outcomes from AR and VR interventions; however, issues including technology usability, adherence, and methodological limitations are noted. This review underscores the significant potential of AR and VR interventions in healthcare, but emphasizes the need for more rigorous research to address current gaps in the clinical effectiveness and application.